Comparative Study of Occupational Burnout and Job Stress of Frontline and Non-Frontline Healthcare Workers in Hospital Wards during COVID-19 Pandemic - Farnaz Etesam; Mitra Akhlaghi; Zahra Vahabi; Samaneh Akbarpour; Mohammad Hossein Sadeghian (Tehran University of Medical Sciences, 2021)
Background: Paying attention to the issue of mental health in the workplace, especially with current pandemic conditions of COVID-19 is of significant importance. Therefore, this study aimed to determine the factors affecting occupational burnout among health care center staff during the pandemic of coronavirus infection. Methods: The present study was a case-control study carried out in the first half of the year 2020 on medical staff working in hospitals in Tehran. The sample size was 324 individuals, including 175 employees working in general (non-COVID) wards and 149 people working in COVID-19 wards. Demographic characteristics questionnaire and two standard questionnaires of Maslach Burnout Inventory and Parker and DeCotiis Job Stress Scale were distributed. Results: Total score of job stress and its two dimensions (time and pressure) had a significant relationship with different levels of occupational burnout. Logistic regression analyses showed significant relations between job stress with emotional exhaustion (95% CI, 1.11-1.19, OR=1.15) and depersonalization. Participants in both wards experienced statistically significant increasing trends given the different components of occupational burnout concurrently by increasing their total stress score. Conclusion: Hospital staff's levels of stress and occupational burnout regardless of where they worked (COVID-19 wards or general wards) were not significantly different and existed among the members of both groups. On the other hand, job stress and its dimensions (time pressure and anxiety) had a significant relationship with the main dimensions of occupational burnout.